Electric susceptibility of sodium-doped water clusters by beam deflection - Carrera, Alvaro Daniel (2009)
The electric susceptibility of neutral sodium-doped water clusters Na(H2ON, N = 6-33, was determined by beam electric deflection. The clusters behave as polarizable particles; their intensity profiles exhibit global shifts toward the high-field region without the occurrence of broadening. In the conditions of the experiment, sodium-water clusters have a "floppy" structure and hence the electric susceptibility presents both electronic and orientacional terms. Measured susceptibilities are somewhat higher than those of pure water clusters, and the contribution per water molecule is similar for both cluster types.